Accidental Finding of Suspected Cysticercosis Without Symptoms in Balinese Male: A Case Report - Satya Pranata, Anak Agung Ngurah; I Made Suma Wirawan; Anak Agung Istri Sri Kumala Dewi (HM Publisher, 2024)
Background: Cysticercosis is one of the illnesses that the WHO considers to be neglected tropical diseases (NTD). Prevalence of cysticercosis in Asia ranged from 0.8% to 41.8%. Mostly, the central nervous system is affected. Case presentation: A 56-year-old Balinese male came to emergency department with main complaint weakness on right-side of his body since 12 hours before being admitted to the hospital. He has history of eating lawar (Balinese traditional food) mixed with fresh pig blood; the last time he ate it was 6 months. Chest examination no nodule/swelling, abscess, or hypertrophy of muscle was found. On laboratory examination WBC 7.47x103/ul, Hb 16.0 g/dL, percentage of eosinophil 5.4%, and eosinophil count 0.40x103/ul. Head CT without contrast suggesting sub-acute cerebral infarction in the left capsule internal. The patient then performed chest radiograph and accidentally multiple rice grain calcification was found. The patient treated with albendazole 15mg/kg/bb/day for 14 days. Clinical presentations of cysticercosis can vary from those with no symptoms to those symptomatic, Patients with muscular involvement are mostly asymptomatic. Increasing eosinophil in complete blood count may indicate helminth infection, to clinch the early diagnosis radiological modalities can be used. However histological findings will give a definitive diagnosis. The use of praziquantel and albendazole is the suggested antihelminth in cysticercosis. Conclusion: Pulmonary muscle involvement of cysticercosis is a rare finding. Increasing awareness of such lesions may lead to early diagnosis and prevent irreversible damage.